1996
DOI: 10.1002/(sici)1099-1166(199612)11:12<1111::aid-gps437>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Geriatric Nurses? Attitudes Towards the Use of Nasogastric Feeding-Tubes in Demented Patients

Abstract: Geriatric nurses’ attitudes towards the use of nasogastric feeding‐tubes in severely demented patients were evaluated. A questionnaire was administered to 232 geriatric nurses asking whether they would favour enteral feeding for demented patients who were unable or refused to eat. The great majority of nurses (73.3%) were favourable; previous experience with nasogastric feeding‐tubes and a moderate to high level of religiosity were both significantly associated with this attitude. For the great majority (70.6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Some healthcare professionals (particularly nurses) believe feeding is a basic human requirement that should not be denied, irrespective of cognitive function. 22,23 By contrast, physicians experienced in the care of the elderly are less willing to favour any form of tube feeding in severely demented patients. 24 In Canadian studies, 30% of carers who had consented to PEG insertion subsequently expressed uncertainty about whether the right decision had been made.…”
Section: Ethical Dilemmas In Peg Feeding Demented Patientsmentioning
confidence: 99%
“…Some healthcare professionals (particularly nurses) believe feeding is a basic human requirement that should not be denied, irrespective of cognitive function. 22,23 By contrast, physicians experienced in the care of the elderly are less willing to favour any form of tube feeding in severely demented patients. 24 In Canadian studies, 30% of carers who had consented to PEG insertion subsequently expressed uncertainty about whether the right decision had been made.…”
Section: Ethical Dilemmas In Peg Feeding Demented Patientsmentioning
confidence: 99%
“…Nurses tended to have a more positive than negative attitude towards administering artificial food and fluid therapy. The percentages of proponents varied widely from 18%,44 26%,42 and 51%,36 to about 73%,35 39 whereas the percentages of opponents ranged from 10%,42 and 27%35 39 to 62% 44…”
Section: Resultsmentioning
confidence: 97%
“…The articles of Wurzbach37 38 represent two publications derived from the same study; therefore, we considered them as one study. Five studies were classified as being qualitative,24 28 35 37 38 41 and eight were classified as being quantitative 33 34 36 39 40 4244. We also identified one mixed-method study that used both qualitative and quantitative approaches 29.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 -11 In 1996, a study on 232 Italian geriatric nurses evaluated their attitude towards the use of enteral nutrition in severely demented patients, finding that a great majority of them (73.3%) favored the use of FTs regardless of the severity of patient's mental status. 10 More recently, Lubart and colleagues 11 found that NH staff and patients' relatives are often ambivalent toward FT use, on the one hand believing that it is an essential procedure for delivering food and fluids for life support, but on the other hand fearing that FT use may prolong a life of suffering. In this light, it should be hypothesized that the cultural leadership of NH physicians may have played a critical role for counterbalancing the attitudes of nurses and relatives towards the use of FT. Another factor that may be related to low FT use in our facilities is the presence of a team of trained volunteers.…”
Section: To the Editormentioning
confidence: 99%